Automatic Cleaning System of Chicken Coop - Muhammad Alif Fathiraihan; Purba Daru Kusuma (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
A This study aims to develop an automated cleaning system for chicken coops using Internet of Things (IoT) technology. The system utilizes IoT technology to monitor and control the condition of the coop in real-time and provide notifications to the farmer through a mobile application. The main specifications of the system include scheduled feeding, system status monitoring, alarm notifications, and database communication. The system utilizes Arduino Mega 2560 + Wi-Fi built in Esp8266 as the microcontroller, in case of any discrepancies in the system status, such as low food or water capacity, the system triggers alarms or sends notifications to the mobile application. Additionally, the system operates continuously for 24 hours and maintains communication with the database to ensure up-to-date information. It also features an automated cleaning function that can schedule regular cleaning of the coop using water. The farmer can control the cleaning process through buttons located near the coop. During the system verification, the scheduled Cleaning, status alert feature, system uptime, communication between the system and the database, and automated cleaning functionality were tested and verified according to the specified requirements. This research provides a practical and efficient solution for managing broiler chicken coops. The system allows real-time monitoring of coop conditions, improves cleaning efficiency, and enhances coop cleanliness. Implementing this system can boost farm productivity and facilitate overall coop management.